Analisis Pengembangan Kelembagaan dan Sistem Produksi Benih Padi di Jawa Tengah - Teguh Prasetyo; Munir Eti Wulanjari; Cahyati Setiani (Universitas Muhammadiyah Purworejo, 2022)
Seeds in the rice production system have an important role, namely as a means of production that affects productivity. Therefore, programs to fulfill the production and need for seeds always receive adequate attention. To determine the development of rice seed conditions in Central Java, an analysis of institutional development and seed production systems in Central Java was carried out. The results of the analysis show that there are four main actors in seeds that play a role in the development of the rice production system, namely (1) policy and program makers (2) research and breeders (3) seed producers and distributors (4) seed supervision and certification. The functions and duties of these institutions are different but interrelated and lead to farmers as end consumers of seed users. During the 2014 - 2018 period, seed production in Central Java was in the range of 38,250 - 38,667 tons, while the planting area for the same period was 1,804,761 - 1,991,680 ha, if the average seed requirement per hectare was 30 kg/hectare. ha, which means the need for seeds is in the range of 46,138 - 49,138 tons. In terms of rice seed production, during the 2014-2018 period there was a seed shortage of around 20 - 28%, however, there were no complaints by farmers about the shortage of seeds. One of the reasons is that rice seed is a substitute product and it is difficult to detect the distribution of seeds, so it is not possible to know with certainty the availability of seeds in Central Java. Related to this, it is time to build a rice seed information system in Central Java that can be accessed by stakeholders, the intention is to know for sure the traffic and availability of rice seeds in Central Java. If from the class of seeds produced it can be seen that 85 -94% are seed class seeds (SS), this shows that most of them use seed class seeds as seeds for consumption rice production.